PCR Positivity of Gerbils and Their Ectoparasites for Leishmania Spp. in a Hyperendemic Focus of Zoonotic Cutaneous Leishmaniasis in Central Iran - Sahar Azarmi; Alireza Zahraei-Ramazani; Mehdi Mohebali; Yavar Rassi; Amir Ahmad Akhavan; Amrollah Azarm; Omid Dehghan; Samira Elikaee; Rahimeh Abdoli; Mohsen Mahmoudi (Journal of Arthropod-Borne Diseases, 2023)
Background: Various arthropods, including Rhipicephalus sanguineus and Ctenocephalides felis felis have been suggested as secondary vectors of Leishmania spp. many years ago. This study was conducted to determine zoonotic cutaneous leishmaniasis (ZCL) PCR positivity of reservoir hosts and their ectoparasites for Leishmania spp. in Segzi plain in Esfahan Province from October 2016 to October 2017.